Unraveling the Relation Between Reading Comprehension and Print Exposure. Issue 5 (15th November 2019) - Erbeli, Florina; van Bergen, Elsje; Hart, Sara A.
Abstract : The purpose of this study was to test the directionality of influence between reading comprehension (RC) and print exposure (PE), thereby estimating genetic and environmental effects of this relation. The sample consisted of 910 twins in fourth through ninth grades ( M age  = 12.33 years, SD  = 1.41) from the Florida Twin Project on Reading, Behavior, and Environment. Using direction‐of‐causation model in a twin design, results supported a direction of influence running from RC to PE. This relation was underpinned by genetic and environmental factors of RC as well as PE. Implications for reading education are discussed.